(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
Efforts of the communists and Communist Party of Malaya (CPM) in influencing the Malay community in Peninsular Malaysia began in the 1920s. These efforts began with the presence of communist agents from Indonesia attempting to influence the Malays to join the communist movement in the Malay states. These efforts continued during the Japanese occupation through the establishment of the Malayan People’s Anti-Japanese Army (MPAJA) or "Three Stars". Hence, communist efforts could be seen during the Emergency through to the establishment of a Malay militant group, that is, the 10th Malay Regiment in Pahang in 1949. Although the CPM’s first movement (1948-1960) was not successful, the CPM did not despair in their struggle. Thus, when the CPM re-emerged in Peninsular Malaysia in June 1968, they continued with their efforts to influence the Malays. To that end, the communists spread the propaganda that communism and Islam could work together for the advancement of the Malay community. They were present at mosques and prayed together with the Malays. However, the efforts of the communists were not well received by the Malay community who held fast to Islam. Their failure to secure the support of the Malays eventually led to their defeat and hence the failure of the CPM to gain control of Malaysia. Keywords: Communist Party of Malaya, communist movement, Malay community, 10th Malay Regiment, propaganda